A Study on the Geotechnical Properties of Coal Ash after a Long Term Service Period in Transport Embankment Fill. Issue 1 (January 2021) - Maakoe, Tshegofatso; Deng, Jianliang; Nepal, Dikshit Babu; Simango, Annah
Abstract: An extensive range of studies have been conducted on coal-fired power station CCP's in order to investigate their geotechnical properties for construction of structural fills. Many such researches are based on the performance of fresh ash, however very few have studied their behavior after a long term service period. There exists a rarely discussed CCP ash that was identified in this investigation. Understanding of the long term behavior of CCP's is essential for motivation of their use in structural fills. This ash was used as an alternative to natural soils for the construction of transport embankment layerworks in countries such as the USA and South Africa. Several decades later after its use in railway embankment fills, the geotechnical properties are evaluated in this study by method of experimental investigation. A series of tests (particle size distribution analysis, specific gravity, compaction and permeability) were carried out with the objective of characterizing the material and determining the shear strength behavior by direct shear test. Test results revealed that the ash is comparable to a granular soil. The direct shear test results revealed that the ash exhibited a significantly high shear strength by the internal friction angle of 51.86°. Furthermore, a reversal and re-shearing of the sample was completed and presented a slightly lowered residual friction angle of 49.37°.